The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/aac.00487-19
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Inhibition of the Extended-Spectrum β-Lactamase PER-2 by Avibactam

Abstract: The diazabicyclooctane (DBO) avibactam (AVI) reversibly inactivates most serine-β-lactamases. Previous investigations showed that inhibition constants of AVI toward class A PER-2 are reminiscent of values observed for class C and D β-lactamases (i.e., k2/K of ≈103 M−1 s−1) but lower than other class A β-lactamases (i.e., k2/K = 104 to 105 M−1 s−1). Herein, biochemical and structural studies were conducted with PER-2 and AVI to explore these differences. Furthermore, biochemical studies on Arg220 and Thr237 var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…These enzymes have been reported to be inhibited by avibactam to a lesser extent than other class A β-lactamases, with significant differences in MIC values for avibactam and relebactam when tested in combination with other β-lactams. 85 , 91 More detailed studies are warranted due to the difference in activity of these two inhibitors of the same class. Recent analysis demonstrated that A. baumannii isolates harbouring PER enzymes can display elevated MIC values against cefiderocol, a siderophore cephalosporin.…”
Section: Esbl Familiesmentioning
confidence: 99%
“…These enzymes have been reported to be inhibited by avibactam to a lesser extent than other class A β-lactamases, with significant differences in MIC values for avibactam and relebactam when tested in combination with other β-lactams. 85 , 91 More detailed studies are warranted due to the difference in activity of these two inhibitors of the same class. Recent analysis demonstrated that A. baumannii isolates harbouring PER enzymes can display elevated MIC values against cefiderocol, a siderophore cephalosporin.…”
Section: Esbl Familiesmentioning
confidence: 99%
“…Only one isolate (K. oxytoca co-harbouring NDM, PER-2 and CIT) showed an AZT-AVI MIC of 8 mg l −1 , which is categorized as intermediate by the CLSI AZT breakpoint. Ruggiero et al [16] demonstrated that PER-2 is not as efficiently inhibited by AVI as other class A β-lactamases. PER-2 represents the second most frequent ESBL in Argentina [17] (5 % of E. coli oxyiminocephalosporin resistant), but its presence in international surveillance studies is minor.…”
Section: Discussionmentioning
confidence: 99%
“…The results reveal a distinctive kinetic profile for AmpC EC inhibition by ZID, which differs from those observed for AVI, REL, and NAC. Together with studies on the inhibition of class A, D and other, structurally distinct class C SBLs (16,19,20,(31)(32)(33) the results will help guide further optimization of the DBO scaffold for potent broad spectrum SBL inhibition.…”
Section: Downloaded Frommentioning
confidence: 95%
“…While the interactions of avibactam with a wide variety of SBLs have been studied (e.g. (24)(25)(26)(27)(28)(29)(30)), structural information on the binding of other DBOs is more limited (16,19,20,(31)(32)(33).…”
Section: Downloaded Frommentioning
confidence: 99%